Use of Moringa Leaf Tea as A Potential Local Resource in Stunting Prevention in Kemerleng Village, Linge District - Fajri, Maulidilfajri; Maulana, Herdi Rianda; Angkat, Kaseana; Wulandari, Enda; Desnita, Desnita; Rauzah, Rauzah; Rehan , Rehan (Pencerah, 2024)
This activity aims to assist the people of Kemerleng Village, Linge District, in utilizing Moringa leaf tea and the potential of local resources as an effort to prevent stunting. The approach used involves outreach and education to increase public awareness of the importance of balanced nutrition and the use of local plants that are rich in nutrients. One of the main focuses is to introduce Moringa leaf tea as an innovative product that can support stunting prevention. This activity also aims to provide insight to the public about the benefits of Moringa leaves which have high nutritional content, even though up to now they have only been considered an ordinary or wild plant. During the implementation of the program, it was found that factors causing stunting included a lack of attention to nutritional needs for pregnant women, low awareness of the importance of child nutrition, and a lack of public attention to children's growth and development as a whole. Through the socialization carried out, the community gave a positive response and showed increased understanding. regarding the benefits of Moringa leaves as a food ingredient with high nutritional value. It is hoped that this program can be the first step to build public awareness in preventing stunting based on local potential.